Prevalence of dental caries, cystic lesion of jaws and peri-implantitis in a known population. - Bagchi, Sanjukta; Mohammed Arif, shaik; Sharma, Rekha; Desai, Juhi Puri; Hanchanale, Ojas Basavaraj; Mugloo, Nasir Gulzar (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the prevalence of dental caries, cystic lesion of jaws and peri-implantitis in a known population. Material and methods: This study was conducted in 100 school going children of Bardhamaan city from January 2025-March 2025. All the parents of the children were asked to give consent for the study after being explained the procedure of the study. All the subjects underwent oral clinical examination. The prevalence of dental caries, cysts and peri-implantitis was assessed. The findings were tabulated and compared. Statistical analysis was conducted using SPSS software. Results:In this study, there were total 100 subjects of which 41 had dental caries, 32 had cysts and 27 had peri-implantitis. Group 1 comprised of 41 subjects with dental caries. Group 2 comprised of 32 subjects with cysts. Group 3 comprised of 27 subjects with peri-implantitis. There were total 68 males and 32 females in this study. There were 33 males and 8 females in group1. There were 16 males and 16 females in group 2. There were 19 males and 8 females in group 3. Conclusion:From the results of this study, it can be concluded that the prevalence of dental caries, cysts and peri-implantitis among school children was 41%, 32% and 27%, respectively. There were a greater number of males than females